How do you solve # 6(w - 1) = 3(3w + 5) #?

2 Answers
Jul 29, 2016

Answer:

Use the distributive property, then solve for #w#.

Explanation:

The distributive property states that #a(b+c)=a*b+a*c#. Let's use this on the two parentheses:

#6(w-1)=6*w+6*1=6w+6#

#3(3w+5)=3*3w+3*5=9w+15#

We now have #6w+6=9w+15#.

Next, let's isolate #w# on one side of the equation by subtracting 6 from each side...

#6w=9w+9#

...and subtracting 9w from each side:

#-3w=9#

From here, it's easy. Just divide each side by -3 to get our answer:

#w=-3#

Jul 29, 2016

Answer:

#w=-7#

Explanation:

#6(w-1)=3(3w+5)#
or
#6w-6=9w+15#
or
#9w-6w=-6-15#
or
#3w=-21#
or
#w=-21/3#
or
#w=-7#